Marginality: Addressing the Nexus of Poverty, Exclusion and Ecology - von Braun, Joachim; Gatzweiler, Franz W.; von Braun, Joachim; Gatzweiler, Franz W.; von Braun, Joachim; Gatzweiler, Franz W. (Cham Springer Nature, 2014)
Environment, general; Environmental Law/Policy/Ecojustice; Environmental Economics; Social Policy
English
Keywords: Environmental economics; Manufacturing industries; Public health & preventive medicine; Earth sciences, geography, environment, planning; Environment, general; Environmental Law/Policy/Ecojustice; Environmental Economics; Social Policy